Brucellosis in China: history, progress and challenge - Hai Jiang; David O'Callaghan; Jia-Bo Ding (BMC, 2020)
Abstract Brucellosis is a neglected zoonosis. It causes acute febrile illness and a potentially debilitating chronic infection in humans, and livestock infection has substantial socioeconomic impact. Over the past two decades, improvements have been made to better understand the various aspects of human and animal brucellosis. Meanwhile, especially in the developing world, immense challenges that remain in controlling and eradicating brucellosis are novel diagnostics tools and efficacious vaccines. Here, we will focus on the remarkable issues on epidemiological survey, as well as the priority and challenge of brucellosis in China. Brucellosis will be controlled with meaningful collaboration between local and public partnerships effectively applying a One Health framework.